Study of Fungal Infection at Bath Rooms of Wadi Ashati Student’s Accommodation Brack, Libya (Libyan Journal of Ecological & Environmental Sciences and Technology, 2025)
Fungal contamination of the girl’s student’s accommodation bath rooms at Wadi Ashati University has been studied in this research. Results shows a sever and different fungal contamination at these bath rooms, the level of contamination was 100%. Contamination defers between the residential portions and this is may be because of the hygiene procedure follows at some partitions or the number of residents used these path rooms. Twenty fungal species were isolated from the bath rooms. A. flavus and Penicillium citrinum were the most predominant species which isolated (27.3%) comparing with Alternaria spp., Cladosporium spp., and other Aspergillus and Penicillium strains which presents at (9.0%). The results also indicate that 45.5% of the fungal isolates were from the basin and 27.0% were isolated from the walls between the shower rooms. All mycological media used in the present study can be employed for fungal growth, however there was more luxuriant growth of all the isolates on potato dextrose agar and malt extract agar comparing with Czapek Dox agar.
Keywords: fungal infection; bath rooms; Wadi Ashati student’s; accommodation; Brack; Libya